EW 102 : a second course in electronic warfare - Adamy, David (Artech House radar library., 2004)
Annotation Serving as a continuation of the bestselling book EW 101: A First Course in Electronic Warfare, this new volume is a second installment of popular tutorials featured in the Journal of Electronic Defense. Without delving into complex mathematics, this book gives engineers, defense contractors, managers, and government procurers a basic working knowledge of the technologies deployed in today's electronic warfare (EW) systems. Organized into chapters with new introductory and supplementary material from the author, this unique book includes tutorials on radar characteristics, infrared and electro-optical systems, signal jamming, spectrum spreading, satellite communications, and emitter location systems. A thorough and challenging problem set for each class of EW technology covered in the book, complete with solutions, helps readers to evaluate EW systems and their applications.